Nuclear calcium signaling controls nethyl-CpG-binding protein 2 (MeCP2) phosphorylation on serine 421 following synaptic activity - Buchthal, Bettina; Lau, David; Weiss, Ursula; Weislogel, Jan-Marek; Bading, Hilmar (The journal of biological chemistry, 2012)
The function of MeCP2, a methylated DNA-interacting protein that may act as a global chromatin modifier, is controlled by its phosphorylation on serine 421. Here we show that in hippocampal neurons, nuclear calcium signaling controls synaptic activity-induced phosphorylation of MeCP2 on serine 421. Pharmacological inhibition of calcium/calmodulin-dependent protein (CaM)kinases blocked activity-induced MeCP2 serine 421 phosphorylation. CaM kinase II (CaMKII) but not CaMKIV, the major nuclear CaM kinase in hippocampal neurons, appeared to mediate this phosphorylation event. Biochemical subcellular fractionations and immunolocalization studies revealed that several isoforms of CaMKII (i.e. CaMKIIα, -β, -γ, and -δ) are expressed in the cytosol but are also detectable in the cell nucleus of hippocampal neurons, suggesting that nuclear CaMKII catalyzes MeCP2 serine 421 phosphorylation. Thus, in addition to the classical nuclear calcium-CaMKIV-CREB/CBP (cAMP-response element-binding protein/CREB-binding protein) pathway that regulates transcription of specific target genes, nuclear calcium may also modulate genome-wide the chromatin state in response to synaptic activity via nuclear CaMKII-MeCP2 signaling.